O impacto do aparato institucional na eficiência dos negócios e dos processos empreendedores - Ribeiro, Lucas da Silva (Brasil, 2023)
Entrepreneurship and Innovation have always walked together throughout history. Entrepreneurs are often responsible for creating new products, services and business models, becoming leaders in innovation. They are tolerant to identify market opportunities, take risks and invest in innovative ideas. But, for this, several factors must also work for the promotion of a new enterprise, the support to entrepreneurs in this case is essential to facilitate innovative ideas. This work aims to evaluate the most efficient countries based on their political, social and economic characteristics of fostering entrepreneurship, and verify to what extent they imply in encouraging or limiting entrepreneurial activities in a nation. Therefore, an efficiency model based on Data Envelopment Analysis (DEA) was used, with 16 variables classified into 8 outputs and 8 inputs. Through the use of these data, it was found that the most efficient countries had individuals who were more motivated to start a new business, when the political, economic and social variables were well related to each other, making the promotion of entrepreneurial activity in the country motivated.